Cover Image, Volume 29, Issue 9. (3rd October 2018) - Ma, Jin; Ma, Shiyu; Yin, Chunxia; Wu, Huanlin
Abstract : On the cover : The cover image, by Jin Ma et al., is based on the Original Article Matrine reduces susceptibility to postinfarct atrial fibrillation in rats due to antifibrotic properties, DOI: 10.1111/jce.13448 .